Maqasid-al-Shariah-based socio-economic development index (SCECDI): The case of some selected Islamic economies / Sana Ullah and Adiqa Kausar Kiani - Ullah, Sana; Kiani, Adiqa Kausar (Universiti Teknologi MARA Selangor, 2017)
The main objective of this study is to develop a socio-economic development index (SCECDI), which is composed of social development index (SCDI) and economic development index (ECDI). For the analysis, we have included 14 Islamic countries which are Afghanistan, Bahrain, Bangladesh, Egypt, Indonesia, Iran, Kuwait, Malaysia, Morocco, Pakistan, Qatar, Saudi Arabia, Turkey and U.A.E for the years 2010 and 2015.Pakistan’s spending on education and health is quite low during last five years on average, while value added agriculture is the highest among all Muslim countries. Meanwhile, spending on health and education in Saudi Arabia is quite high, besides having quite high export value added and capital formation. These are required for better economic development. Highest educational profile is observed in Malaysia, while the employment rate is highest in Kuwait among all. We have diversified the summary profile for all countries of the variables included for the analysis in the study. Expected outcome is that those Islamic economies which have better economic conditions, will have more than 0.50 values for SCECDI, while others may have the value in between 0-0.50. We also demonstrate the importance of SCECDI focusing the dynamic characteristics of all Islamic countries included in the study.